MRI as an analytical tool in three models of neuroinflammation - Kelly, Ronan J. (Trinity College (Dublin, Ireland). Department of Physiology, 2012)
It is well established that inflammatory changes in the brain accompany the ageing process and neurodegenerative disorders. These changes are largely mediated by activation of microglial and astrocytic cells, which is characterized by an increase in cell surface markers and the release of pro-inflammatory cytokines. CD200 is a cell surface protein widely expressed on a variety of cells, including neurons, astrocytes and endothelial cells. However, expression of CD200 receptor is reserved for cells of the myeloid lineage, including microglia. Several studies have shown that ligation of the CD200R by its endogenous ligand helps preserve microglia in a quiescent state, and that microglia are restrained from tissue-damaging activation through CD200R signalling.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin